“Plan de protección de las microcuencas Maguazo y Bocatoma como fuentes de captación de agua potable para la ciudad de Riobamba” - Chagñay Lema, Viviana Edith (2018)
Ecuador, like many other countries, suffers a process of degradation of natural resources, including their water sources. This problem is evident from the growth of the population to the urban and rural levels, since, by the desire to achieve a maximum development have exploited the natural resources and services indiscriminately and unconscious, causing serious consequences to the environment. Currently, the water service from the city of Riobamba has nine distribution networks, of which three have continuous distribution, the rest has a intermittent distribution in three hours of supply; this is due to several factors, among them the lack of production flow, both physical and commercial losses and to the lack of a culture of efficient water use; producing discomfort in the community and social conflicts. To overcome these problems, the GADM of Riobamba, made a great investment which will cover this deficit, which consists in the construction of the transfer "Maguazo-Alao" which has as main sources the micro-watersheds of Maguazo and Bocatoma, the same as for the purposes of construction and operation, require an appropriate management plan. With this background, the Municipal GAD of Riobamba and The Universidad Nacional de Chimborazo, through an inter-institutional agreement, raised the present research project, which proposes a coherent solutions to the reality of the area, on the basis of an assessment of the current state of these micro-watersheds, through the development of several logical steps such as: bibliographic analysis, field and laboratory analysis, in addition to the implementation of the SWOT matrix and Leopold; allowing to determine the water quality index (ICA-NSF), the biological Index Ephemeroptera, Plecoptera and Trichoptera (ETP), the Andean Biological Index (ABI) and evaluation of environmental impacts; this being the basis for the establishment of technical alternatives within the protection plan